Analisis Pasangan Calon Tunggal Dalam Pemilihan Kepala Daerah Kota Pematang Siantar Tahun 2020 - Gary Timothy Hasian Purba; Subhilhar Subhilhar; Hatta Ridho (Universitas Medan Area, 2022)
The purpose of this study was to analyze a single candidate pair in the regional head election of Pematang Siantar City in 2020. The purpose of this study was to explain why there was a single candidate pair in Pematang Siantar City. The legality of the Constitutional Court Decision number 100/PUU-XII/2015 is a legal force to uphold the meaning of democracy in political contestation, in this case regional head elections. Besides that, the essence of democracy which promises freedom to be elected and to vote is an additional power to bring up a single candidate pair. The failure to regenerate political parties is another trigger for the emergence of a single candidate pair in the post-conflict local election. Not only in Pematang Siantar City but also throughout Indonesia. The method used in this research is descriptive qualitative with interview instruments involving political party administrators and political observers in Pematang Siantar City in addition to references to single candidate pairs. The weak cadre of political parties with the presence of wholesale parties makes incumbents not get support in Pematang Siantar City. The legal power of the Constitutional Court's decision and the meaning of democracy to be elected and voted made the single candidate pair in Pematang Siantar City win the post-conflict local election against an empty box.